Criminal Sanctions Against Narcotics Traffickers - Prima, Berry; Azhali Siregar, Mhd. (Proceedings of the International Conference on Multidisciplinary Science (INTISARI), 2024)
Drug-related crimes have increasingly become a pressing issue in recent times. Law No. 35 of 2009 on Narcotics lacks specific definitions for categories such as users, sellers, distributors, and dealers, focusing instead on the types and quantities of narcotics. This ambiguity often leads to confusion when determining ownership of illicit substances, as roles among users, owners, and dealers sometimes overlap, particularly when large quantities are involved. In the case of Decision Number: 327/Pid.Sus/2023/PN.Mdn, the imposition of the death penalty on a suspect identified as a drug dealer aligns with Article 114, paragraph (2) of the Narcotics Law. This study employs normative legal research, utilizing statutory and philosophical approaches to explore the application of criminal sanctions for narcotics dealers. The findings reveal that the death penalty is the most severe punishment prescribed for drug dealers, as regulated in Article 114, paragraph (2). In narcotics-related offenses, investigators use evidence as outlined in Article 184 of the Criminal Procedure Code, which includes witness testimonies, expert opinions, documentary evidence, indications, and defendant statements. Article 114, paragraph (2) and Article 119, paragraph (2) of the Narcotics Law specify that individuals involved in offering, selling, buying, brokering, exchanging, transferring, or receiving narcotics in defined quantities and types qualify as dealers and are subject to the death penalty.